Pengaruh Akuntabilitas dan Transparansi terhadap Kepercayaan Masyarakat dalam Pelayanan Pembuatan Surat Ijin Mengemudi (SIM) pada Kepolisian Resort (POLRES) Brebes - Lusia Wulandari Sutejo (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2019)
ABSTRACT This study aims to analyze the effect of accountability and transparency on public trust in the service of making a driving license (SIM) at the Brebes Police Resort (POLRES). The population in this study was 334 people in December 2018. 84 people were taken using the probability sampling technique. The analytical tool used is multiple linear regression with partial test equipment and simultaneous test equipment. The results of the analysis show that the accountability variable has a positive influence on public trust, and the transparency variable has a positive influence on public trust. Taken together, the variables of accountability and transparency have a positive effect on public trust. The transparency variable has a more dominant influence on public trust.Keywords: Accountability, Transparency, and Public Trust